2014
DOI: 10.1111/jocs.12404
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Function Recovery Following LVAD Implantation and Bariatric Surgery in a Morbidly Obese Patient

Abstract: We present a morbidly obese 44-year-old female who underwent Thoratec HeartMate II left ventricular assist device implantation. The patient subsequently underwent laparoscopic sleeve gastrectomy and removal of the LVAD following improvement in her cardiac function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…On the other hand, it is noteworthy that bariatric surgery after LVAD implantation is a safe and feasible option, 43 at times even enabling recovery from the LVAD. 44 …”
Section: In the Internal Medicine Wardmentioning
confidence: 99%
“…On the other hand, it is noteworthy that bariatric surgery after LVAD implantation is a safe and feasible option, 43 at times even enabling recovery from the LVAD. 44 …”
Section: In the Internal Medicine Wardmentioning
confidence: 99%
“…By July 2010, his weight reached a nadir at 106.6 kg, BMI 29. Others have reported cases of complete cardiac functional recovery following LVAD implantation and subsequent bariatric surgery . However, in our patient, despite this significant weight loss, transesophageal echocardiography–guided attempts at LVAD weaning immediately revealed persistence of severe LV failure, and he was listed for transplantation.…”
Section: Patient Profilementioning
confidence: 59%
“…Furthermore, the subsequent reduction in BMI may lead to improvement in cardiac function in morbidly obese patients with severe advanced systolic heart failure . It has been shown that myocardial recovery is possible with LVAD support, and it has been suggested that in conjunction with bariatric surgery, these treatment options may work synergistically . We report a patient who required bariatric surgery for extreme weight gain while supported by an LVAD as a bridge to cardiac transplantation, and discuss the perioperative management of these patients.…”
mentioning
confidence: 97%
“…49 There are other reports on successful cases involving LVAD and bariatric surgery as bridge for heart transplantation 50,51 or improvement in ventricular function in morbidly obese patients. 52 Most references presented in this review showed good results for bariatric surgery in patients with HF. However, it is worth noting that most studies cited were on interventions primarily directed to treat obesity and not eventual cardiac dysfunction, either clinical or suggested by different assessment methods.…”
Section: Bariatric Surgery In Patients With Advanced Hfmentioning
confidence: 81%